Effect of lotus seed powder addition on the physical and organoleptic attributes of chocolate flavour frozen yogurt using goat milk - Maria Azeem; Saba Asim; Awais Raza; Hamad Rasul; Muhammad Ali; Bakhtawar Khalid; Rizwan Shukat; Agoura Diantom (Cogent Food & Agriculture)
This study investigates the impact of lotus seed powder and chocolate addition on the frozen yogurt formulated with goat milk. It’s hypothesized that it would be a low-fat, high-protein, mineral-rich, healthy alternative to market-available dairy frozen desserts. Four different treatments T1 (7% cocoa powder (CP), milk 90%, lotus seed powder (LSP) 3%), T2 (5% CP, 90% milk, 5% LSP) and T3 (3% CP, 90% milk, 7% LSP) were created using lotus seed and cocoa powder, while T0 (100% pure goat milk) was used as the control. The product underwent a comprehensive evaluation, including a thorough assessment of its physicochemical, phytochemical, mineral, and sensory profiles. Prepared yogurt showed an increase in lotus seed powder i.e. 3, 5, and 7% showed reduction in moisture 31.3, 31.5 and 33.7%, respectively. pH ranged from a minimum of 4.41 in T0 to 5.72 in T2. The phytochemical analysis revealed the mean value of TPC, TFC and DPPH of the product in the range of 41.3–87.6 mg/GAE g, 118–147 mg/GAE g, 86–95 µg/mL. The mineral contents ranged 1405–1430 mg/g for Ca, and 149–165 mg/g for Mg. Sensory evaluation of the product revealed that T2 received the highest score for flavor, texture, color, and overall acceptance of the prepared product. Thus, the addition of lotus seed and cocoa powder to goat milk frozen yogurt demonstrated great sensory and nutritional advantages, making it optional for creating a fresh dairy product with high added values.